PROTEIN RAS-LIKE PROTEINS FROM RAT BRAIN SEBAGAI TARGET PENGHAMBATAN PERKEMBANGAN SEL KANKER - SUKANTY, NI MADE WIASTY; SAPUTRA, I PUTU BAYU AGUS; ARIANI, FARIDA; YUNITA, LINA; DEWI, NOVIANTI TYSMALA (GANEC SWARA, 2023)
Ras-like proteins from rat brain (Rab) is one of the crucial proteins in the process of intracellular transport. Rab plays a role in delivering vesicles from the donor membrane to the acceptor membrane. Vesicles contain various molecules that are important in cell growth and development. These molecules are generally involved in some signaling pathways. In carrying out its functions, Rab needs to be activated first. The activation process of Rab involves various proteins. Thus, Rab activation and deactivation control are critical to regulating the movement of the transferred molecules. In cancer, there is an uncontrolled activation and deactivation of Rab. Rab's involvement in various signaling pathways by providing molecules needed for growth and development is a basis for increasing the speed of growth and development of cancer cells. Although Rab is not the main factor causing cancer, it can help the development of cancer. So, it can be one of the keys to controlling the transfer of molecules involved in the growth and development of cancer cells. There are several methods related to the activation of Rab for molecular transport. Rab activation inhibition by Rab inhibitors and inhibitors of Rab activating proteins and the use of miRNAs can prevent molecule transport. Thus, control of Rab activation can be an alternative to suppress the growth and development of cancer cells.